Perspectives of paediatric hospital staff on factors influencing the sustainability and spread of a safety quality improvement programme. Issue 3 (22nd March 2021) - Lachman, Peter; Gondek, Dawid; Edbrooke-Childs, Julian; Deighton, Jessica; Stapley, Emily
Abstract : Objective: Situation Awareness For Everyone (SAFE) is a quality improvement programme aiming to improve situation awareness in paediatric clinical teams. The aim of our study was to examine hospital staff perceptions of the facilitators and barriers/challenges to the sustaining and subsequent spread of the huddle, the key intervention of the SAFE programme. Setting: Interviews were held on two wards in two children hospitals and on two children wards in two district general hospitals. Method: Semistructured interviews were conducted with 23 staff members from four National Health Service paediatric wards. A deductive thematic analysis was conducted, drawing on an existing framework, which groups the factors influencing programme sustainability into four categories: innovation, leadership, process and context. Participants: 23 staff in two children's hospitals and two children's wards across four UK hospitals, comprising of nurses and doctors, administration or housekeeping staff, ward managers and matrons, and allied professionals. Primary outcomes: Understanding factors contributing to the sustaining and spread of a quality improvement intervention. Results: Perceptions of the benefits, purpose and fit of the huddle, team commitment, sharing learning, adaptation of the method and senior leadership were identified as facilitators. High staff turnover, large multiple specialty medical staff teams, lack of senior leadership and dislike of change were identified as barriers/challenges. Conclusions: Sustaining and spreading quality improvement interventions in a complex clinical setting requires understanding of the interplay between the actual innovation and existing leadership, process and contextual factors. These must be considered at the planning stage of an innovation to maximise the potential for sustainability and spread to other settings.